Cloud Computing Challenges in Security Applications – A Review - Joby, P. P. (Recent Research Reviews Journal, 2022)
Cloud computing platforms provide an advanced computer system that allows organizations and individuals to operate a wide range of tasks such as using online storage capacity, implementing business applications, developing customised computer software, and creating a "realistic" communication network. Because of numerous security and privacy concerns, cloud technology has struggled to gain popularity among many large and established organizations. This research discusses the security challenges of cloud computing networks, beginning with a description of cloud computing and its various types. Furthermore, it provides a brief explanation of the most common cloud computing service challenges.